The new Klein-Lacan dialogues - Borossa, Julia; Bronstein, Catalina; Pajaczkowska, Claire (Karnac, 2015)
This book provides a timely exploration and comparison of key concepts in the theories of Melanie Klein and Jacques Lacan, two thinkers and clinicians whose influence over the development of psychoanalysis in the wake of Freud has been profound and far-reaching. Whilst the centrality of the unconscious is a strong conviction shared by both Klein and Lacan, there are also many differences between the two schools of thought and the clinical work that is produced in each. The purpose of this collection is to take seriously these similarities and differences. Deeply relevant to both theoretical reflection and clinical work, the New Klein-Lacan Dialogues should make interesting reading for psychoanalysts, psychotherapists, mental health professionals, scholars and all those who wish to know more about these two leading figures in the field of psychoanalysis. The collection centres around key concepts such as: 'symbolic function', the 'ego', the 'object', the 'body', 'trauma', 'autism', 'affect' and 'history and archives'. The authors are internationally renowned writers and clinicians and include: Eva Bahovec, Lionel Bailly, Rachel Blass, Ronald Britton, Catalina Bronstein, Bernard Burgoyne, Robert Hinshelwood, Roberto Ileyassoff, Marie-Christine Laznik, Elias Mallet da Rocha Barros, Catherine Mathelin-Vanier, Maria Rhode, Elisabeth Roudinesco, Richard Rusbridger, Michael Rustin, Paul Verhaeghe and Marcus Vieria. Re-opening a dialogue first attempted with great success in 1995 ("The Klein-Lacan Dialogues", organised by Catalina Bronstein and Bernard Burgoyne), this book is based on a new international seminar series collaboratively organised by colleagues at UCL, Middlesex University, and the Royal College of Art and held in 2011 under the auspices of the UCL Psychoanalysis Unit.